PEMBUATAN ANIMASI DALAM MENJALANKAN RUKUN ISLAM MENGGUNAKAN APLIKASI 3DS MAX - Adelia Kartika Panggabean; Sumi Khairani; Dharmawati (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
In Islam, there are five pillars that become general guidelines for Muslims. These five pillars are called the Five Pillars of Islam. The Five Pillars of Islam are an important basis that must be known by all Muslims. In delivering this information, technology's role is needed because the development of information technology is currently developing very rapidly. Information is one of the needs that are needed by many people. Animation is one of the media in the delivery of information. With animation, the information conveyed can attract attention and increase motivation because it provides an easier understanding of the information provided. This research aimed to make an animation as an information media in carrying out the Five Pillars of Islam. By utilizing the application from 3DS Max, the information will be packaged in the form of 3D animation, the results will later be used as a medium for education or learning about what and how to carry out the pillars of Islam, especially for converts.